Review of baseline studies on energy policies and indicators in Malaysia for future sustainable energy development - Hannan, Mohammad Abdul; Begum, Rausham Ara; Abdolrasol, Maher G.M.; Mohamed, Azah; Rashid, Muhammad Mahbubur (Elsevier Ltd, 2018)
Malaysia's framework for energy development was established in the early 1970s. Henceforth, many successive policies were introduced as potential resources for electricity generation and utilization. Currently, as a signatory to the United Nations Framework Convention on Climate Change, Malaysia is sparing no eﬀort to comply with the policy to meet the challenges of mitigating over-dependence on fossil fuels, reducing carbon levels, and achieving sustainable national development. This paper reviewsthe baseline studies on electrical energy policies and the measurement indicators used in Malaysia's electric power system. This research involves a comprehensive survey of electrical energy policies in Malaysia that focus on issues pertaining to energy supply, utilization, its environmental impact and considerations, renewable energy (RE) policies, production and consumption, energy eﬃciency, and feed-in tariﬀs. Fourteen energy indicators for sustainable development in Malaysia were investigated through the identiﬁcation of energy policies in signiﬁcant areas, such as reliability, safety, adequacy and cost-eﬀectiveness of energy supply; increasing energy eﬃciency; minimizing environmental impact; and enhancing quality of life in terms of social well-being. The policies and the indicators are classiﬁed into diﬀerent sustainable dimensions and summarized in tables along with the corresponding key references. In this study, future energy planning and options, especially in nuclear and RE programs, as well as the conﬂictbetweenthem,areillustratedthroughtheoverallperformancerelativetotargetsandbenchmarksfor past and future projections up to the year 2030. This review seeks to examine the past, present, and future policies and indicators to provide a suﬃcient overview of Malaysian energy policies for optimizing sustainable development. The goal is for this review to lead to increased eﬀorts to accommodate the increasing demand for the management and utilization of RE, promote energy eﬃciency, and improve performance in achieving sustainable national development